Structural characteristics of crab burrows in Hong Kong mangrove forests and their role in ecosystem engineering. (5th January 2021) - Agusto, Laura Elisabeth; Fratini, Sara; Jimenez, Pedro J.; Quadros, Aline; Cannicci, Stefano
Abstract: Crab burrowing activity impacts several important biogeochemical processes within mangrove forests. Burrow morphology has been shown to be variable between brachyuran families, hence the community structure and composition of burrowing crabs may have the potential to impact ecosystems differently. By increasing belowground surface area, volume and bacterial microhabitats, large and complex burrows may differ from smaller and simpler burrows in their impact to nutrient and organic matter distribution. The central aim of this work was to provide a detailed quantification of the scale to which different mangrove crab families impact Hong Kong mangrove ecosystem through their burrowing activities. To achieve this goal, we recorded burrow densities and described specie-specific burrow morphology, through casts and 3D scans, of eight crab species belonging to four families, across three mangrove forests. Where present, the large and complex burrows of Parasesarma bidens (Sesarmidae) increased the total below ground air-sediment surface area per m 2 by ~190% and accounted for ~1.9% of excavated volume per m 3 of mangrove sediment. On average, the burrows of Metaplax spp. (Varunidae) increased the surface area by ~55%, while the ocypodid and dotillid species accounted for a 10–25% increase across sites. Due to its densities and the complexity of its burrows, P. bidens showed to exert a wide impact on Hong Kong mangrove ecosystems unrivalled by other species. By incorporating species-specific burrow characteristics and actual burrow densities, we were able to accurately estimate the differential bioengineering role of the dominant mangrove crab species. Due to the functional role of crab bioengineering, our estimates are critical to assess Hong Kong mangrove ecosystem functioning and health. Graphical abstract: Image 1 Highlights: Casting, 3D scanning and density surveys of burrows of Hong Kong mangrove crabs. Burrow morphology determines the role of seven crab species in total bioturbation. Bioturbation and sediment reworking differ across and within mangrove areas. Burrows of a single species, Parasesarma bidens doubled air-sediment surface area.